К экологии анаэробных азотфиксаторов рода Clostridium в водоёмах среднего Днепра - Михайленко, Л.Е. (Гидробиологический журнал, 1966)
Цель настоящей работы изучить распространение анаэробных азотфиксаторов рода Clostridium в различных водоемах среднего Днепра в связи с условиями обитания. Устанавливалось также отношение исследуемых микроорганизмов к высшей водной растительности. В настоящем сообщении представлены данные, собранные в русле Днепра (у сс. Григоровка, Бучаки и Васильков), в затонах Беловод и Васильков и в пойменном озере Верхний Уступ. A study of the distribution of anaerobic nitrogen-fixing bacteria of the genus Clostridium in the Middle Dnieper basins in connection with the habitat conditions reveals a number of regularities. In channel areas, where the temperature, pH and 02 are practically the same throughout the body of water owing to the current, the vertical distribution of the investigated bacteria was mainly uniform; their numbers were 25— 600 cells/ml. The increase in numbers of the investigated bacteria in the benthic layers, observed in some cases, was due to conditions of higher reduction. In the backwaters of the Dnieper and in the flood-plain lake, non-uniform vertical distribution of the investigated bacteria was noted in all cases. The increase in their numbers at the bottom by 2—4000 times is due to the conditions of higher reduction in connection with a considerable decrease in oxygen content and some decrease in pH. The increase in the numbers of investigated bacteria in the basins is correlated in a number of cases with the increase in the contents of organic matter of vegetable origin and of total nitrogen. The presence of anaerobic nitrogen-fixing bacteria of the genus Clostridium on the surface of higher aquatic plants and in their rhizosphere indicates that their relationship is of a symbiotic nature, and that the investigated bacteria play an important part in supplying the plants with nitrogen.